Aortic dissection with concomitant acute myocardial infarction: From diagnosis to management - Lentini, Salvatore (Medknow Publications, 2011)
Acute aortic dissection an extremely severe condition having a high risk of mortality. The classic symptom may mimic other conditions such as myocardial ischemia, leading to misdiagnosis. Coronary malperfusion associated with aortic dissection is relatively rare, but when it occurs, it may have a fatal result for the patient. The diagnosis of acute coronary syndrome may lead to the inappropriate administration of thrombolytic or anticoagulant treatment resulting in catastrophic consequences. Emergency imaging techniques help to guide the correct diagnosis. Transthoracic echocardiography is useful as a first imaging test, and may be followed by transesophageal echocardiography, or other imaging techniques. Surgery represents the treatment for these patients. However, with the aim to stabilize the patient and to reduce myocardial damage, initial preoperative endovascular coronary intervention has been reported.